2021
DOI: 10.17230/ad-minister.39.2
|View full text |Cite
|
Sign up to set email alerts
|

How gender and age can affect consumer purchase behavior? Evidence from A microeconomic perspective from Hungary

Abstract: The present study aimed to investigate the effect of demographic variables of gender and age on online consumer purchase behavior (CPB) on Facebook in Hungary. The statistical population of the present study consists of Facebook users in Hungary, including Hungarian natives, foreigners residing in this country including students. A sample of 433 online consumers in different age groups was surveyed. The questionnaire was shared via an online link on the Facebook platform and also on various channels. Welch’s t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
14
1
Order By: Relevance
“…There was a significant difference between consumer purchase behavior in all age groups and the age group over 50 years on Facebook. This important result emphasized the importance and impact of social networks as marketing channels on young people (Fakete-Farkas et al, 2021;Sorce et al, 2005) found that age did not impact consumer purchase behavior, and it is contrary to the results of a particular study. Different marketing strategies and approaches are necessary for the different consumer age segments in E-Commerce showed the results of the study (Nemati & Khajeheian, 2018).…”
Section: The Use Of Marketing In the Context Of Different Age Consumerscontrasting
confidence: 63%
“…There was a significant difference between consumer purchase behavior in all age groups and the age group over 50 years on Facebook. This important result emphasized the importance and impact of social networks as marketing channels on young people (Fakete-Farkas et al, 2021;Sorce et al, 2005) found that age did not impact consumer purchase behavior, and it is contrary to the results of a particular study. Different marketing strategies and approaches are necessary for the different consumer age segments in E-Commerce showed the results of the study (Nemati & Khajeheian, 2018).…”
Section: The Use Of Marketing In the Context Of Different Age Consumerscontrasting
confidence: 63%
“…The inter-class correlation (ICC) coefficient value was confirmed in terms of consistency (Bouzari et al 2021;Fekete-Farkas et al 2021;Ebrahimi et al 2020) to determine the reliability of sampling.…”
Section: Data Collectionmentioning
confidence: 97%
“…, 2019; Ebrahimi et al. , 2021a, b; Fekete-Farkas et al. , 2021), their validity is confirmed (Table 2).…”
Section: Analysis and Resultsmentioning
confidence: 54%
“…Convergent validity for the research constructs was assessed using AVE criteria. Since the AVE values for three structures were above 0.5 The effect of internal branding (Hair et al, 2019;Ebrahimi et al, 2021a, b;Fekete-Farkas et al, 2021), their validity is confirmed (Table 2). However, values above 0.4 are acceptable if discriminant validity is not compromised (Ebrahimi and Mirbargkar, 2017).…”
Section: Analysis and Resultsmentioning
confidence: 72%